The Effect of Delivery Timeliness, E-WOM,¬ and Trust on Consumer Satisfaction of E-Commerce Users Bibli.com - Erry Alberth; Hikmah Hikmah (Pusat Riset dan Inovasi Nasional, 2026)
Increasing competition in the e-commerce industry requires companies to continuously improve the quality of service in order to achieve and maintain customer satisfaction. Customer satisfaction is an important indicator of an organization's success, as it directly affects customer loyalty and long-term business sustainability. This study aims to analyze the influence of delivery timeliness, electronic word of mouth (E-WOM), and trust on customer satisfaction on Blibli.com e-commerce platforms. This study adopts a quantitative approach with an explanatory research design. Data were collected through the survey method by distributing a structured questionnaire to active users Blibli.com who met the predetermined research criteria. Data analysis was carried out using inferential statistical techniques to examine partial and simultaneous effects among the research variables. The results showed that delivery timeliness, E-WOM, and trust each had a positive and significant effect on customer satisfaction when partially tested. In addition, these three independent variables simultaneously show a significant influence on customer satisfaction. These findings suggest that ensuring on-time delivery performance, effectively managing online consumer reviews and information, and strengthening customer trust are strategic factors that should be prioritized by Blibli.com to improve customer satisfaction and strengthen competitiveness in the highly dynamic e-commerce industry.